PARASPINAL MUSCLE DENERVATION AND BALANCE IMPAIRMENT IN LUMBAR SPINAL STENOSIS - YAĞCI, İLKER (WILEY-BLACKWELL, 2016)
Introduction: Denervation of the paraspinal muscles may impair posture and displace the center of gravity. Therefore, we assessed balance impairment in patients with lumbar spinal stenosis (LSS) with and without paraspinal denervation. Methods: Thirty-two women with LSS (15 symptomatic, 17 asymptomatic), aged 42-78 years, were assessed for disability, pain, and mobility, and underwent masked mini-paraspinal mapping (mPSM). Berg Balance Scale (BBS) and device-assisted balance (DAB) tests were used for balance assessment. Results: The symptomatic group had worse balance and higher mPSM scores than the asymptomatic group. Among DAB tests, limit of stability (LOS) had the highest correlations with BBS and mPSM in the symptomatic group. Conclusions: Paraspinal denervation correlated highly with static and dynamic balance in symptomatic patients. We recommend paraspinal mapping, balance assessment, rehabilitation, and follow-up with the LOS test for symptomatic patients.
Keywords: balance; denervation; limits of stability; lumbar spinal stenosis; paraspinal mapping; paraspinal muscles; LOW-BACK-PAIN; CLINICAL-EXPERIENCE; CANAL STENOSIS; COMMUNITY; SYMPTOMS; FALLERS; PERFORMANCE; NONFALLERS; LIMITS; SCALE